2020
DOI: 10.3233/jad-200061
|View full text |Cite
|
Sign up to set email alerts
|

Blood Amyloid-β Oligomerization as a Biomarker of Alzheimer’s Disease: A Blinded Validation Study

Abstract: INTRODUCTION: Oligomeric amyloid ß (Aß) is one of the major contributors to the pathomechanism of AD; Aß oligomerization in plasma can be measured using a Multimer Detection System-Oligomeric Aß (MDS-OAß) after incubation with spiked synthetic Aß. METHODS: We evaluated the clinical sensitivity and specificity of the MDS-OAß values by inBlood TM OAß test using heparin-treated plasma samples from 52 AD patients in comparison with 52 community-based subjects with normal cognition (NC). The inclusion criterion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…AD group (n=27) was differentiated from age-matched normal control group (n=144) with AUC of 0.896 (sensitivity 83.3%, speci city 90.0%) [5]. A recent validation study with AD (n=52) and normal control (n=52) con rmed the diagnostic accuracy with AUC value of 0.999 (sensitivity 100%, speci city 92.31%) [6]. The current study was completed in more heterogeneous population including individuals with AD, MCI, SCD, or other neurodegenerative diseases, and predictability on amyloid PET positivity was comparable (AUC 0.855).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…AD group (n=27) was differentiated from age-matched normal control group (n=144) with AUC of 0.896 (sensitivity 83.3%, speci city 90.0%) [5]. A recent validation study with AD (n=52) and normal control (n=52) con rmed the diagnostic accuracy with AUC value of 0.999 (sensitivity 100%, speci city 92.31%) [6]. The current study was completed in more heterogeneous population including individuals with AD, MCI, SCD, or other neurodegenerative diseases, and predictability on amyloid PET positivity was comparable (AUC 0.855).…”
Section: Discussionmentioning
confidence: 90%
“…All tests were completed in duplicate and the average was used. 0.78 ng/ml was established as the cut-off value in the previous validation study and the plasma OAβ concentration equal to, or higher than the cut-off value was de ned as MDS-OAβ positive [6]. MDS-OAβ tester was blinded to clinical information including demographics and diagnosis.…”
Section: Blood Sampling and Mds-oaβ Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Youn et al [ 77 ] reported further improvement of the AβO amplification technique. The analysis was conducted using commercially available kit (inBlood™ OAβ test), produced by People Bio Inc, Korea.…”
Section: Techniques Based On Amplification Of Misfolded Protein Conformationsmentioning
confidence: 99%
“…An “ideal” biomarker should be (1) able to detect a fundamental feature of AD neuropathology, (2) validated in neuropathologically confirmed AD cases, (3) precise (able to detect AD early in its course and distinguish it from other dementias), (4) reliable, (5) non-invasive, (6) simple to perform, (7) inexpensive. Appearance of polymeric forms of Aβ in CSF and blood is a unique feature of AD, and recent data reviewed above [ 73 , 77 ] indicate that analysis of AβO levels possesses a great potential for discriminating between AD and other types of neurodegenerative and neurological disorders with sufficient sensitivity and specificity. Use of blood plasma rather than CSF opens a possibility for non-invasive sampling of biological material.…”
Section: Amyloid-β Oligomers In Plasma: a Promising Candidate To «Ideal» Diagnostic Marker For Ad?mentioning
confidence: 99%